.........................
Пошаговое объяснение:
.................
ответ: х = 3 целых 5/6
Для начала дроби переведем в неправильные:
46/27 : (х - 23/18) *45/38 = 15/19
46/27 : (х - 23/18) = 15/19 * 38/45 =2/3
х - 23/18 = 46/27 * 3/2 =23/9
х = 23/9 + 23/18
х = 69/18 = 23/6
х = 23/6 = 3 целых 5/6
.........................
Пошаговое объяснение:
.................
ответ: х = 3 целых 5/6
Пошаговое объяснение:
Для начала дроби переведем в неправильные:
46/27 : (х - 23/18) *45/38 = 15/19
46/27 : (х - 23/18) = 15/19 * 38/45 =2/3
х - 23/18 = 46/27 * 3/2 =23/9
х = 23/9 + 23/18
х = 69/18 = 23/6
х = 23/6 = 3 целых 5/6